1996
DOI: 10.1002/(sici)1096-9861(19961007)374:1<118::aid-cne9>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of somatostatin immunoreactive neurons in the medial cerebral cortex and other cortical areas of the lizardPodarcis hispanica

Abstract: The ontogeny of somatostatin immunoreactive interneurons in the cerebral cortex of the lizard Podarcis hispanica has been studied in histological series of embryos, perinatal specimens, and adults. Somatostatin immunoreactive interneurons appear in the early stages of lizard cerebral cortex ontogeny, their number increases during embryonary development, reaches a peak in early postnatal life, and decreases in adult lizards. The first somatostatin immunoreactive somata in the lizard forebrain appeared on E36, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 111 publications
0
11
0
Order By: Relevance
“…According to this hypothesis, the primordial plexiform layer (preplate)-derived subplate and marginal zone are the 'reptilian framework' of the mammalian cerebral cortex 118 , and a preplate is present during development of the dorsal cortex in reptiles 119 . Thus, the subplate originated as an embryonic structure before the appearance of the neocortex and the inversion of the cortical neurogenetic gradient observed in mammals.…”
Section: Box 1 | Evolution Of the Subplatementioning
confidence: 99%
“…According to this hypothesis, the primordial plexiform layer (preplate)-derived subplate and marginal zone are the 'reptilian framework' of the mammalian cerebral cortex 118 , and a preplate is present during development of the dorsal cortex in reptiles 119 . Thus, the subplate originated as an embryonic structure before the appearance of the neocortex and the inversion of the cortical neurogenetic gradient observed in mammals.…”
Section: Box 1 | Evolution Of the Subplatementioning
confidence: 99%
“…Their neuronal populations share many similarities, but also display minor differences (see Nacher et al, 1996). Table 3 summarizes the main resemblances between medial cortex projection neurons of Podarcis, and dentate granule cells of the hippocampal formation of different mammalian species.…”
Section: Comparative Aspects: Mammalsmentioning
confidence: 99%
“…However, in the Tarentola mauritanica, the majority of newborn cells seemed to be incorporated into MC (Perez-Canellas & Garcia-Verdugo 1996), which is considered as an area homologous to dentate gyrus of hippocampus in mammals on grounds of their anatomy, cyto-and chemoarchitecture and postnatal development (Lopez-Garcia et al 1992;Nacher et al 1996), and closely involved with learning and memory (Day et al 2001;Rodriguez et al 2002); DVR in Trachemys scrypta was found to show the most intensive labeling accumulation (Perez-Canellas et al 1997). It is possible that these interspecific differences may depend on behavioral patterns induced by distinct environmental stimuli.…”
Section: Regional and Interspecific Differences In Adult Neurogenesismentioning
confidence: 99%